The necessity of geneticist and pulmonologist collaboration in the treatment of monogenic interstitial lung diseases in adults - Sterclova, Martina; Doubkova, Martina; Doubek, Michael; Macek, Milan (Breathe (Sheffield, England), 2025)
Interstitial lung diseases (ILDs) are a very heterogeneous group of diseases. Although the aetiology of many of these diseases is not fully understood, an association with specific pathogenic gene variants has been demonstrated for some of the diseases. The aim of this review is to provide genotype-phenotype correlation information on monogenic ILDs to provide guidance to pulmonologists on when to refer ILD patients for genetic testing. Most patients with monogenic ILDs suffer from multiorgan involvement and should be managed by a multidisciplinary team of specialists. Different syndromes are associated with a greater risk of (nonrespiratory) malignancies (Birt-Hogg-Dubé syndrome and telomeropathies). Isolated lung involvement has been described in surfactant-related gene variant carriers (SFTPA 1 and 2, SFTPC) and patients with pulmonary alveolar microlithiasis. The clinical suspicion of monogenic ILDs should be raised in young patients diagnosed with ILD, patients with a known family history of ILD or suspected telomeropathies, and patients suspected of having syndromes associated with ILD. Patients with suspected monogenic ILDs should be aware of the possibility of genetic counselling both to obtain a diagnosis and to select further follow-up by pulmonologists and other involved specialists. Raising awareness of monogenic ILDs and creating counselling platforms is necessary both to diagnose and manage patients with these rare diseases.